Pengelolaan Sampah di TPS3R Pandan Bersih Desa Pudak Kecamatan Kumpeh - Syarifuddin, Hutwan; Hamzah; Jalius; Hamidah, Afreni (JCOMMITS: Journal of Community Empowerment, Inovation, and sustainability, 2023)
The waste handling program is one of the efforts to maintain the cleanliness of the environment and reduce pollution. Training activities on waste management and maggot cultivation through Community Service (CS) aim to increase knowledge, insight, and care for the environment and village entrepreneurship through the Pandan Bersih Non-Community Group (NCG). The Community Service activities provide skills to NCG and the surrounding community to process waste (organic and inorganic) and maggot cultivation, thereby increasing selling value and environmentally friendly products. Based on the results of the evaluation conducted on the training participants, this activity is needed, especially in maintaining the cleanliness of the environment and reducing the stench from garbage. Participants felt that so far their knowledge was still very limited. In the future, it is expected that other programs in processing inorganic waste, such as plastic into con blocks, paving blocks and fuel, will produce environmentally friendly maggots.